A research on the use of metaphor design in promoting brand identity - Ipaki, Bahram; Movahedi, Yazdan; Jourabchi Amirkhizi, Parisa (Journal of Graphic Engineering and Design, 2018)
Every new brand which competes and increases its market share needs some tools and methods to be applied to its products. The objective of this research is to investigate the use of metaphor as a tool for peak shift effect and its impact on memory, which can be effective in promoting brand identity from a customer perspective. In this respect, this research uses a combination of memory test and comparison of two objects method. Therefore, the research method was according to environment specifications. The results indicated that the products having metaphor in comparison to products with no metaphor has an effective role in peak shift and image persistence and its name in user’s mind. In conclusion, the brand identity can be promoted in a variety of ways, among which the design of metaphor, which is related to product design and graphic design, is one of these ways.